(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Respiratory diseases in children represent both a medical and social problem, with their annual increase necessitating the improvement of existing approaches and the introduction of new strategies for diagnosis, treatment, and prevention.